2020
DOI: 10.1186/s12931-020-01459-0
|View full text |Cite
|
Sign up to set email alerts
|

The need for a holistic approach for SSc-ILD – achievements and ambiguity in a devastating disease

Abstract: Systemic sclerosis (SSc) is a multi-organ autoimmune disease with complex interactions between immune-mediated inflammatory processes and vascular pathology leading to small vessel obliteration, promoting uncontrolled fibrosis of skin and internal organs. Interstitial lung disease (ILD) is a common but highly variable manifestation of SSc and is associated with high morbidity and mortality. Treatment approaches have focused on immunosuppressive therapies, which have shown some efficacy on lung function. Recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 83 publications
0
19
0
8
Order By: Relevance
“…SSc-ILD should be managed by a multidisciplinary team [ 80 ]. Among non-pharmacologic options, pulmonary rehabilitation is aimed at improving lung function [ 81 ]; in particular, when an SSc-ILD patient is being considered for a transplant, pulmonary rehabilitation is a necessary step in their evaluation [ 81 ].…”
Section: Other Treatment Optionsmentioning
confidence: 99%
“…SSc-ILD should be managed by a multidisciplinary team [ 80 ]. Among non-pharmacologic options, pulmonary rehabilitation is aimed at improving lung function [ 81 ]; in particular, when an SSc-ILD patient is being considered for a transplant, pulmonary rehabilitation is a necessary step in their evaluation [ 81 ].…”
Section: Other Treatment Optionsmentioning
confidence: 99%
“…SSc is a connective tissue disease characterized by early microvascular impairment, skin, and internal organ fibrosis (19)(20)(21)(22)(23)(24)(25)(26). Several studies have also recently demonstrated an increased risk of OP in SSc patients, correlated with multiple factors, i.e., low vitamin D levels (1,5,13,15,27).…”
Section: Tbs and Systemic Sclerosismentioning
confidence: 99%
“…Schon lange ist bekannt, dass auch andere fibrosierende ILD, allen voran die chronische exogen-allergische Alveolitis (EAA), die Sarkoidose und ILD im Rahmen von verschiedenen Autoimmunerkrankungen trotz adäquater Diagnose und – zumeist immunsuppressiver – Therapie einen progredient fibrosierenden Verlauf mit einer ebenso unvorteilhaften Prognose aufweisen können [ 1 , 9 12 ].…”
Section: Introductionunclassified
“…Klassisch hierfür ist die systemische Sklerose (SSc), die sich in 70–80 % in der Lunge manifestiert, was zu einer substanziellen Prognoseeinschränkung führt [ 12 14 ]. Für die SSc-ILD wurde in den Scleroderma Lung Studies I und II die Wirksamkeit von Cyclophosphamid und Mycophenolat-Mofetil (MMF) nachgewiesen, wobei sich MMF als nebenwirkungsärmer herausstellte [ 15 , 16 ].…”
Section: Introductionunclassified
See 1 more Smart Citation